The Result of Price Perception, Product Quality, Delivery Quality, Discount Program on the Decision of Scaffolding Rental Mediated by Word of Mouth at PT. Pamungkas Putra Pratama - Habibi, Ansor; Zulfitri Zulfitri (Dinasti International Journal of Digital Business Management, 2023)
The marketing strategy is the most important thing to overcome the fast business competition. This study aims to determine the result of perception, price, product priority, delivery, discount program, on rental choices Scaffolding mediated by word of mouth at PT. Pamungkas Putra Pratama. The method used in this study is a quantitative method with a correlation approach. The populations in this study are all customers of PT. Pamungkas Putra Pratama collected data using a questionnaire or questionnaire distributed to each member of the population. The data analysis technique is by measuring the Likert scale using the SEM analysis of the Smart PLS software. The results of this study indicate that perceptions of price, product priority, delivery, and discount programs have a significant and positive result on the choice to rent scaffolding at PT Pamungkas Putra Pratama. Perception, price, product priority, delivery and discounts also have a positive and significant impact on word of mouth at PT. Pamungkas Putra Pratama. Therefore word of mouth is capable and influential in increasing scaffolding rental choices at PT. Pamungkas Putra Pratama.